Capturing Dissipation Charge in Charge Space Accumulation Area for Enhancing Output Performance of Sliding Triboelectric Nanogenerator. Issue 31 (5th July 2022) - He, Wencong; Shan, Chuncai; Wu, Huiyuan; Fu, Shaoke; Li, Qianying; Li, Gui; Zhang, Xuemei; Du, Yan; Wang, Jian; Wang, Xue; Hu, Chenguo
Abstract: The charge space‐accumulation effect is one of most effective strategies to boost output performance of the sliding mode triboelectric nanogenerator (TENG) with AC output, by which the shielding layer greatly prevents the air breakdown on the sliding interface and the blank triboarea with charge dissipation on its surface promotes charge accumulation. However, charge dissipation speed depends on the properties of materials and these charges are lost in the air. Herein, a novel strategy is proposed to capture dissipation charge in charge space accumulation area for further enhancing output performance of the sliding TENG. DC output electrodes based on the coupling of triboelectrification and air‐breakdown is designed on both sides of the slider to quickly and completely collect the dissipation charge on the stator and accumulated charge on dielectric tribolayer of slider. Hence, the device has multichannel output to improve output charge to 98%. A new recorded average power density of 5.74 W m –2 Hz –1, 14 times higher than previously reported, is obtained. The coupling relationship between AC and DC output is systematically studied. This work provides a new idea for improving the output and energy harvesting efficiency of TENGs. Abstract : A novel strategy to capture dissipation charge in a charge space accumulation area is proposed for further enhancing output performance and the energy conversion efficiency of sliding triboelectric nanogenerators (TENGs). The charge space accumulation effect and charge capture strategy are utilized to obtain both AC output via electrostatic induction and DC output via air‐breakdown. Hence, a multichannel output and double output mode TENG is obtained.